Matching on Gender and Sexual Orientation - Edoardo Ciscato; Marion Goussé (Institute of Labor Economics (IZA), 2024)
We study the mating patterns of non-heterosexual individuals, who represent a significant and increasing portion of the population, particularly among the youth. We estimate a multidimensional matching model of the marriage market where partner's gender is endogenously chosen conditional on the agent's sexual orientation, and is subject to trade-offs that depend on both the agents' preferences and the pool of potential partners. We show that same-sex couples experience lower gains from live-in relationships, a "same-sex penalty". Absent this penalty, the share of same-sex couples in the U.S. would increase by about 50% (from 1.36% to 2.05% of all couples).
Keywords: D1; C51; J12; J15; 330; matching; marriage market; homogamy; same-sex households; sexual orientation; gender